Effect of modified rubber powder on the morphology and thermal and mechanical properties of blown poly(lactic acid)–hydroxyl epoxidized natural rubber films for flexible film packaging - Chor Wayakron Phetphaisit (2020)
© 2019 Wiley Periodicals, Inc. In this study, we prepared and used modified natural rubber powder to increase the toughness of poly(lactic acid) (PLA) films. We blended PLA and hydroxyl epoxidized natural rubber (HENR) via a melt-mixing process with twin-screw extruder and a blowing machine. We investigated the influence of the HENR content in the blend films on the microstructure, thermal, mechanical, and optical properties. The morphology of the blend showed a coarse surface and elongated fibrils of HENR in the PLA matrix. After blowing, the dispersion of small particles of HENR in the substrate was seen. The size of the remaining HENR particles was smaller than that of the starting powder. The compatibility of HENR and the remaining rubber particles may have synergistically contributed to improvements in the elongation at break, impact strength, and ultraviolet–visible transition protection of the PLA films. The elongation at break drastically increased from 3 to 228% after PLA was blended with 20 wt % HENR. On the other hand, all of the blends exhibited lower glass-transition temperatures and cold crystallization temperatures than the pure PLA films. We concluded that the blend was partially compatible and may have increased the flexibility of the PLA films. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 136, 47503.